Given
∫ 0 ∞ ( 1 + x 2 ) 2 x ( 1 − x 2 ) ln ∣ ∣ ∣ ∣ x − 1 x + 1 ∣ ∣ ∣ ∣ d x = b π a − d π c ,
find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i dont understand the transformation x--- 1/x
this is genius man!!
Problem Loading...
Note Loading...
Set Loading...
Split the integral as follows:
∫ 0 1 ( 1 + x 2 ) 2 x ( 1 − x 2 ) ln ( 1 − x 1 + x ) d x + ∫ 1 ∞ ( 1 + x 2 ) 2 x ( 1 − x 2 ) ln ( x − 1 x + 1 ) d x
In the second integral, perform the transformation x ↦ x 1 to obtain:
∫ 0 1 x 1 ( 1 + x 2 1 − x 2 ) 2 ln ( 1 + x 1 − x ) d x
Next, use the substitution 1 + x 1 − x = t ⇒ d x = ( 1 + t ) 2 − 2 d t i.e
∫ 0 1 1 − t 1 + t ( 1 + t 2 ) 2 4 t 2 ln t ( 1 + t ) 2 2 d t = 8 ∫ 0 1 ( 1 − t 2 ) ( 1 + t 2 ) 2 t 2 ln t d t = I
From integration by parts and using the following result:
∫ ( 1 − t 2 ) ( 1 + t 2 ) 2 t 2 d t = 8 1 ( 1 + t 2 − 2 t − ln ( 1 − t ) + ln ( 1 + t ) ) + C
⇒ I = ( ( 1 + t 2 − 2 t − ln ( 1 − t ) + ln ( 1 + t ) ) ln t ∣ ∣ ∣ ∣ 0 1 − ∫ 0 1 ( 1 + t 2 − 2 t − ln ( 1 − t ) + ln ( 1 + t ) ) t 1 d t
Notice that the first term is zero i.e
I = ∫ 0 1 1 + t 2 2 d t + ∫ 0 1 t ln ( 1 − t ) d t − ∫ 0 1 t ln ( 1 + t ) d t
⇒ I = J 1 + J 2 − J 3
J 1 = ∫ 0 1 1 + t 2 2 = 2 ( arctan t ∣ 0 1 = 2 π
J 2 = ∫ 0 1 t ln ( 1 − t ) d t = − k = 1 ∑ ∞ k 1 ∫ 0 1 t k − 1 d t = − k = 1 ∑ ∞ k 2 1 = − 6 π 2
J 3 = ∫ 0 1 t ln ( 1 + t ) d t = − k = 1 ∑ ∞ k ( − 1 ) k ∫ 0 1 t k − 1 d t = − k = 1 ∑ ∞ k 2 ( − 1 ) k = 1 2 π 2
Hence,
I = 2 π − 6 π 2 − 1 2 π 2 = 2 π − 4 π 2